Die Christensklaven in Algier/Nordafrika: Eine Episode aus den Herrnhuter Missionsanfängen - Manukyan, Arthur (Unitas Fratrum, 2018)
The article deals with the attempts of Abraham Ehrenfried Richter and Carl Nottbeck between 1738 and 1748 to undertake missionary work among the Christian slaves of Algiers. Their aim was pastoral and social work among seafarers who had been enslaved. From 1745 Nottbeck held services in his accommodation in Algiers and looked after some citizens of Hamburg, most probably Lutherans, who had been enslaved, but also quite a few Roman Catholics. The author examines the relationship between Europe and North Africa in the early modern period, considers the problem of piracy by the socalled ‘Barbary states', and illustrates the fate of such slaves with the example of Hark Olufs. Der Autor draws a fascinating picture, characterized by both cultural conflict and cultural contact in North Africa, which lay beyond the reach of European law, and where the total of about one million Christian slaves became a not insignificant economic factor. He argues for greater use of the as yet unevaluated Moravian sources, but also describes the problem posed by their perspective being limited to missionary and diaconal concerns.